DYNAMICS OF THE SHIFT OF THE FUNCTION OF THE RELIGIOUS TAKLIM ASSEMBLY IN THE WOMEN'S COMMUNITY IN PALEMBANG CITY - Badaruddin, Kms; Zailia, Siti; Antasari, Rr Rina (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The existence of the Taklim Council as a religious institution with distinctive Indonesian characteristics, with a fairly large number of female congregants and growing almost evenly throughout Indonesia, has received attention and appreciation from many parties. The State has even acknowledged the existence and role of the Taklim Council as stated in the National Education System Law, where the Taklim Council is a form of non-formal educational institution. As well as its important role in cultivating faith and devotion. Its quite populist existence is not only known in rural areas but also in urban areas. However, many people still view its existence as merely a routine activity as an alternative activity for women to utilize their free time and remaining years. Therefore, most of the congregation is a group of housewives aged 30 years and over and also elderly. In fact, the activities of the Taklim Council are only considered as part of compensation activities for various life problems faced by women, especially in domestic life